Analisis Internalisasi Nilai-Nilai Fikih Muamalah dalam Transaksi Jual Beli di Lingkungan Sekolah: Studi Kasus Kelas IX MTs Al-Jauhar - AnisahFadhila Azri; Rian Vebrianto (Fakultas Pendidikan IAI Pangeran Dharma Indramayu, 2026)
The research focuses on the application of fiqh muamalah, which pertains to Islamic jurisprudence related to transactions, in the context of buying and selling activities, specifically within a school setting. The study aims to explore how well students apply the values of fiqh muamalah that they have learned in class, particularly in the school canteen. The methodology of this study uses a mixed-methods approach; the research involved 40 respondents from grade IX MTS students and 2 certified fiqh teachers. Data collection methods included questionnaires, observations, and interviews, allowing the researchers to gather comprehensive insights by engaging directly with participants in their environment. Findings from the study indicate that students are capable of applying the principles of fiqh muamalah in their daily transactions, demonstrating a notable commitment to honesty. This is evidenced by their behaviors in the school canteen, where they prioritize orderly payment and avoid incurring debts. The conclusion drawn from the research emphasizes that grade IX MTS students successfully internalize the teachings of fiqh muamalah in their everyday interactions. The study also suggests that to enhance the application of these values, teachers and school administrators should implement stricter supervision during transactions in the canteen. The researchers recommend that teachers and school administrators maintain strict oversight of students during payment processes to ensure that the principles of fiqh learned in class are fully integrated into their behavior in the cafeteria.